2008
DOI: 10.1080/02844310801987685
|View full text |Cite
|
Sign up to set email alerts
|

Surgical technique for the treatment of radial wrist pain

Abstract: Chronic radial wrist pain with no radiographic evidence of scapholunate instability or other wrist disease can be difficult to diagnose and treat. Our purpose was to evaluate the results of an operation to treat chronic radial or periscaphoid wrist pain that has failed to respond to conservative treatment. We examined the scapholunate ligament and performed a dorsal capsulodesis. One hundred-and-two patients were reviewed retrospectively. Casenotes were available for 88 patients. Function, pain, range of movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The degree of joint contracture correlates to patient functional status, and grip strength is commonly used in upper extremity outcomes studies, with 80% relative strength often established as a benchmark. [9][10][11] Additionally, all patients were screened for post-operative limited joint mobility (LJM) using the Prayer Sign. This clinical examination was performed by having the patient place his or her hands together with the goal of pressing the palms of the hands and palmar surfaces of the interphalangeal joints together.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of joint contracture correlates to patient functional status, and grip strength is commonly used in upper extremity outcomes studies, with 80% relative strength often established as a benchmark. [9][10][11] Additionally, all patients were screened for post-operative limited joint mobility (LJM) using the Prayer Sign. This clinical examination was performed by having the patient place his or her hands together with the goal of pressing the palms of the hands and palmar surfaces of the interphalangeal joints together.…”
Section: Methodsmentioning
confidence: 99%
“…(1) In the same year, Wollstein et al published the results of dorsal capsulodesis for radial wrist pain in 88 patients; 80% of their patients described improvement in pain and function, while 25% required further operation. (4) VanHeest et al, who described partial distal resection of the extensor retinaculum in five athletes with dorsal wrist pain in hyperextension, reported complete pain relief and full return to sports in all five athletes. (8) In 2012, Tan et al found that arthroscopic debridement alone could achieve improvement in wrist pain in patients with intercarpal and TFCC tears.…”
Section: Discussionmentioning
confidence: 99%
“…(4) As the evaluation of chronic wrist pain is challenging, thorough history-taking and physical examination are essential. (5) Although some patients respond to conservative treatment, a subset continues to have chronic pain even with conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A triangular capsular flap is formed through a dorsal approach to the wrist, with the base of the triangle located over the radial aspect of the radioscaphoid joint. 4 The radioscaphoid joint is inspected, including the surfaces of the radius and radial styloid and the proximal and radial scaphoid surfaces.…”
Section: Surgical Techniquementioning
confidence: 99%